Seroprevalence and clinical profile of scrub typhus in patients presenting with undifferentiated acute febrile illness in a tertiary care centre - Jose, Reena Anie; Jose, Hyma; Jacob, Anjali Anne; Thomas, Pramod; Mathew, Renu; Thomas, Marina (Asian Journal of Medical Sciences, 2021)
Background: Scrub typhus (ST) is a common Rickettsial infection which has been increasingly reported from the various states of southern part of India. Aims and Objective: With very few reports from Central Kerala, we aimed to study the seroprevalence of scrub typhus and its clinical profile. Materials and Methods: Patients presenting with acute undifferentiated febrile illness and other symptoms and signs of Rickettsial infections during a period of two years were included in this prospective study. Serodiagnosis of ST was based on a positive Scrub typhus IgM Enzyme Linked Immunosorbent Assay (ELISA) and/or agglutination for OXK in Weil Felix test. The cut-off for ELISA was calculated. The clinical and laboratory details of the positive patients were obtained and bivariate analysis was performed. Results: The cut-off for ST IgM ELISA was calculated and found to be 0.38. Of the 636 samples screened, 34 (5.3%) were positive for ST IgM ELISA. Out of the 34 positive samples, only 5 (0.8%) were positive by Weil Felix test. Most of the ST patients presented during the months of May to January. Rashes were observed in 8.8% of the ST patients and none had signs of eschar. The commonest clinical features included fever, myalgia (52.9%), nausea & vomiting (32.4%), headache (29.4%) and hepatosplenomegaly (29.4%). The commonest abnormal laboratory finding and complication observed were elevated serum transaminases (52.9%) and acute respiratory distress syndrome (17.6%) respectively. Conclusion: The seroprevalence of ST in Central Kerala was 5.3% using Weil Felix test and ST IgM ELISA.